The Influence of Personality Types on the Consumptive Behavior of E-commerce Users (Shopee, TikTok Shop, and Tokopedia) (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of the Big Five Personality traits on the compulsive buying behavior of e-commerce users, with a particular focus on popular platforms such as TikTok Shop, Tokopedia, and Shopee. Compulsive buying behavior, often characterized by excessive and uncontrolled purchasing, has become increasingly prevalent in the digital marketplace, raising concerns regarding consumer well-being and financial management. To investigate this issue, a quantitative approach was employed through a survey distributed to active e-commerce users. The collected data were analyzed using multiple linear regression to examine the extent to which personality traits contribute to compulsive buying tendencies. The findings reveal that the Big Five Personality traits collectively explain 42.6% of the variance in compulsive buying behavior, highlighting their substantial role in shaping consumer decision-making. Among the traits, Neuroticism emerges as the most influential predictor, indicating that individuals with higher emotional instability are more likely to engage in compulsive purchasing as a coping mechanism for stress or negative emotions. Extraversion also shows a significant positive relationship, suggesting that socially outgoing individuals may be driven by the appeal of online interactions, trends, and peer recommendations. Similarly, Agreeableness exerts a notable influence, as more agreeable individuals tend to place higher trust in sellers, advertisements, and social endorsements, thereby increasing their vulnerability to compulsive purchases. In contrast, Openness to Experience and Conscientiousness do not exhibit significant effects, implying that creativity, curiosity, or self-discipline are less relevant in predicting compulsive buying within the e-commerce context. These findings carry important implications for both scholars and practitioners. For marketers, understanding the psychological underpinnings of consumer behavior can inform the development of more ethical marketing strategies, while also providing insights into targeted campaigns. At the same time, consumer education programs aimed at enhancing self-control and financial literacy are essential to mitigate the negative consequences of compulsive buying in the digital era.